Tracheal extubation under Narcotrend EEG monitoring at different depths of anesthesia after tonsillectomy in children: a prospective randomized controlled study - An, Hongqiang; Zhang, Xifeng; Chen, Lingling (Frontiers in Pediatrics, 2024)
Objective: We assume that tracheal extubation at different depths of anesthesia by Narcotrend EEG (NT value) can influence the quality of recovery from anesthesia and cognitive function of children with tonsillotomy.The subjects of the study were 152 children who underwent tonsillotomy with anesthetized with endotracheal intubation in our hospital from September 2019 to March 2022. The enrolled patients were divided into Group A (conscious group, NT range of 95~100), Group B (light sedation group, NT range of 80~94) and Group C (conventional sedation group, NT range of 65~79). A neonatal pain assessment tool: face legs activity crying consolability(FLACC) was used to compare pain scores of different groups as primary end point. Mini-Mental State Examination (MMSE) scale and Montreal Cognitive Assessment (MoCA) scale were used to evaluate the cognitive function of children in different groups before and after surgery as secondary end points.Results: There were differences in the awakening time and FLACC scores after awakening among the three groups of children (P<0.05). Among them, the awakening time was significantly shorter, and the FLACC score after awakening was significantly higher in group A than those in group B and group C (both P<0.05). The total incidence of adverse reactions in group B was significantly lower than that in group A and group C (P<0.05).There was no significant difference in MMSE and MoCA scores before operation and at 7d after operation among the three groups (P>0.05); while a significant difference was found in MMSE and MoCA scores at 1d and 3d after operation among the three groups (P<0.05). In addition, MMSE and MoCA scores of patients in the three groups decreased significantly at 1d and 3d after the operation than those at 1d before the operation (P<0.05).When the NT value of tonsillectomy is between 80 and 94, tracheal catheter removal can effectively improve the recovery quality and improve postoperative cognitive dysfunction of children.